Oncolytic effect of Newcastle disease virus AF2240 strain on the MCF-7 breast cancer cell line. - Othman , Fauziah; Ideris, Aini; Motalleb, Gholamreza; Eshak, Zulkapli; Rahmat, Asmah (Royan Institute, 2010)
Objective: This study was carried out to investigate the oncolytic effect of the Newcastle disease virus (NDV) strain AF2240 on the MCF-7 breast cancer cell line.